Usability of a novel digital medicine system in adults with schizophrenia treated with sensor-embedded tablets of aripiprazole - Peters-Strickland T; Pestreich L; Hatch A; Rohatagi S; Baker RA; Docherty JP; Markovtsova L; Raja P; Weiden PJ; Walling DP (Neuropsychiatric Disease and Treatment, 2016)
Timothy Peters-Strickland,1 Linda Pestreich,1 Ainslie Hatch,2 Shashank Rohatagi,1 Ross A Baker,1 John P Docherty,2 Lada Markovtsova,1 Praveen Raja,3 Peter J Weiden,4 David P Walling5 1Otsuka Pharmaceutical Development & Commercialization, Inc., 2ODH, Inc., Princeton, NJ, 3Proteus Digital Health, Inc., Redwood City, CA, 4Department of Psychiatry, University of Illinois, Chicago, IL, 5CNS Network, LLC, Long Beach, CA, USA Objective: Digital medicine system (DMS) is a novel drug–device combination that objectively measures and reports medication ingestion. The DMS consists of medication embedded with an ingestible sensor (digital medicine), a wearable sensor, and software applications. This study evaluated usability of the DMS in adults with schizophrenia rated by both patients and their health care providers (HCPs) during 8-week treatment with prescribed doses of digital aripiprazole.Methods: Six US sites enrolled outpatients into this Phase IIa, open-label study (NCT02219009). The study comprised a screening phase, a training phase (three weekly site visits), and a 5-week independent phase. Patients and HCPs independently rated usability of and satisfaction with the DMS.Results: Sixty-seven patients were enrolled, and 49 (73.1%) patients completed the study. The mean age (SD) of the patients was 46.6 years (9.7 years); the majority of them were male (74.6%), black (76.1%), and rated mildly ill on the Clinical Global Impression – Severity scale (70.1%). By the end of week 8 or early termination, 82.1% (55/67) of patients had replaced the wearable sensor independently or with minimal assistance, based on HCP rating. The patients used the wearable sensor for a mean (SD) of 70.7% (24.7%) and a median of 77.8% of their time in the trial. The patients contacted a call center most frequently at week 1. At the last visit, 78% (47/60) of patients were somewhat satisfied/satisfied/extremely satisfied with the DMS.Conclusion: A high proportion of patients with schizophrenia were able to use the DMS and reported satisfaction with the DMS. These data support the potential utility of the DMS in clinical practice. Keywords: adherence, antipsychotics, aripiprazole, digital medicine, schizophrenia, usability